Enhancing understanding of SARS-CoV-2 infection among individuals with Down syndrome: an integrative review - Silva, Maria Vitoria Gomes da; Pereira, Laura Resende Guimarães; Avó, Lucimar Retto da Silva de; Germano, Carla Maria Ramos; Melo, Débora Gusmão (São Paulo Medical Journal, 2025)
BACKGROUND: Down syndrome (DS) is a non-rare genetic condition that affects approximately 1 in every 800 live births worldwide. Further, it is associated with comorbidities, anatomical alterations of the respiratory tract, and immunological dysfunctions that make individuals more susceptible to respiratory infections. OBJECTIVE: To systematize the current scientific knowledge about the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among individuals with DS. DESIGN AND SETTING: This integrative review was conducted at the Universidade Federal de São Carlos, São Paulo, Brazil. METHODS: This review was conducted in the following databases: the Virtual Health Library (Biblioteca Virtual em Saúde, BVS), PubMed, and Web of Science, using MeSH descriptors. The search included English or Portuguese studies published between January 1, 2020, and October 14, 2022. RESULTS: A total of 55 articles from 24 countries were selected, comprising 21 case-control or cohort studies, 23 case reports or series, and 11 narrative reviews or opinion studies. The articles were grouped into five categories: previous comorbidities, coronavirus disease 2019 (COVID-19) clinical features and evolution, cytokine storm and interleukins, living in institutions as a risk factor, and behavioral actions as a protective factor against SARS-CoV-2 infection. CONCLUSION: Individuals with DS are more susceptible to COVID-19 infection due to variables such as previous comorbidities, immunological factors, and their habitable environments. These aspects confer a higher risk of infection and an unfavorable clinical course. The precise pathways involved in the pathophysiology of COVID-19 in individuals with DS are not clear, thus requiring further studies. SYSTEMATIC REVIEW REGISTRATION: The Open Science Framework registered the research protocol (https://osf.io/jyb97/).